MAXIMUM REPETITION PERFORMANCE AFTER DIFFERENT ANTAGONIST FOAM ROLLING VOLUMES IN THE INTER‐SET REST PERIOD - Monteiro, Estêvão Rios (Int J Sports Phys Ther, 2017)
BACKGROUND: Foam rollers, or other similar devices, are a method for acutely increasing range of motion, but in contrast to static stretching, do not appear to have detrimental effects on neuromuscular performance. PURPOSE: The purpose of this study was to investigate the effects of different volumes (60 and 120 seconds) of foam rolling of the hamstrings during the inter‐set rest period on repetition performance of the knee extension exercise. METHODS: Twenty‐five recreationally active females were recruited for the study (27.8 ± 3.6 years, 168.4 ± 7.2 cm, 69.1 ± 10.2 kg, 27.2 ± 2.1 m(2)/kg). Initially, subjects underwent a ten‐repetition maximum testing and retesting, respectively. Thereafter, the experiment involved three sets of knee extensions with a pre‐determined 10 RM load to concentric failure with the goal of completing the maximum number of repetitions. During the inter‐set rest period, either passive rest or foam rolling of different durations (60 and 120 seconds) in a randomized order was employed. RESULTS: Ninety‐five percent confidence intervals revealed dose‐dependent, detrimental effects, with more time spent foam rolling resulting in fewer repetitions (Cohen's d of 2.0 and 1.2 for 120 and 60 seconds, respectively, in comparison with passive rest). CONCLUSION: The results of the present study suggest that more inter‐set foam rolling applied to the antagonist muscle group is detrimental to the ability to continually produce force. The finding that inter‐set foam rolling of the antagonist muscle group decreases maximum repetition performance has implications for foam rolling prescription and implementation, in both rehabilitation and athletic populations. LEVEL OF EVIDENCE: 2b